Analysis of Kinang Jingkion Material as Road Subbase Layer Using Soil Cement Method - Rio Andrew Kristio Kandai; Bahtiar Bahtiar; Yohanes B. J. Rusmanta; Harmonis Rante; Apolo Safanpo; Janviter Manalu (Publikasi Indonesia, 2024)
This research aims to analyze the California Bearing Ratio (CBR) and Unconfined Compressive Strength Test (UCS) values as road foundation layers using local materials, namely Kinang Jingkion. The soil and Kinang Jingkion materials for the study were taken from the Apalapsili quarry in Yalimo Regency. Additionally, the additive or soil stabilizer used was matos obtained from the testing of soil characteristics, including sieve analysis or gradation, Standard Proctor Test for light density, and liquid limit test. After testing, it was found that the soil from the Apalapsili quarry is granular soil and can be categorized as A-1-a according to SNI 03-6797-2002. Subsequent testing involved CBR and UCS testing on Mix Designs made of soil and cement with concentrations of 4%, 6%, and 8%. Next, additional Mix Designs were created with compositions of Kinang Jingkion, soil, cement at 4%, 6%, and 8%. Further Mix Designs included compositions of Kinang Jingkion, soil, matos at 2%, and cement at 4%, 6%, and 8%. From the UCS testing results, Mix Designs with soil and cement concentrations of 4% and 6% did not meet the compressive strength criteria, with compressive strength values of 9.26 Kg/Cm² and 17.4 Kg/Cm² respectively. According to SNI 6887-2012, the compressive strength value after 7 days of immersion should be within 25-35 Kg/Cm², while other Mix Designs met the criteria of SNI 6887-2012. CBR testing also utilized the same Mix Designs, and the highest CBR result was obtained from the Mix Design with compositions of Kinang Jingkion, soil, cement at 8%, and matos at 2%, with a CBR value of 112%. According to the 2018 Revised General Specifications, a CBR value of 112% indicates a Class A Foundation Layer.